Testing the Value of Prickly Pear Cactus as a Nest-Predator Deterrent for Northern Bobwhite - Fidel Hernandez; Scott E. Henke; Nova J. Silvy; Dale Rollins (National Quail Symposium Proceedings, 2017)
Recent research indicates that northern bobwhites (Colinus virginianus) in Texas commonly nest in prickly pear cactus (Opuntia sp.) instead of conventional bunchgrass habitat. We hypothesized that bobwhites nested in prickly pear because it served as a deterrent to nest predators thereby increasing probability of nest success (nest-protection hypothesis; Slater et al. 2001). We experimentally tested the nest-protection hypothesis by providing 50 wild-caught, captive raccoons (Procyon lotor) with combinations of simulated, bobwhite nests. Nest combinations included either 1 nest in bunchgrass (e.g., little bluestem [Schizachryium scoparium]) and 1 nest in prickly pear cactus (partial [75%] or full [100%] protection), or 2 separate nests in prickly pear (partial and full protection). Raccoons depredated 97%, 33%, and 14% of simulated nests constructed of bunchgrass (n = 35 nests), partial protection prickly pear (n = 30 nests), and full protection prickly pear (n = 35 nests), respectively. Prickly pear nests that provided full protection exhibited better survival against raccoon depredation than other nest types. Our study provides support for the nest-protection hypothesis regarding why northern bobwhite possibly nest in prickly pear cactus.
Keywords: cactus; Colinus virginianus; nest; northern bobwhite; predation; Procyon lotor; raccoon